Neonatal pain scales study: A Kendall analysis between eye-tracking and literature facial features - Tamanaka, Fernanda G.; Carlini, Lucas P.; Heideirich, Tatiany M.; Balda, Rita C. X.; Barros, Marina C. M.; Guinsburg, Ruth; Thomaz, Carlos E. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2021)
Newborns (NBs) feel pain and the more premature they are, the more immature are their pain attenuation system. Facial expression recognition is a non-invasive method to identify and evaluate their feelings, since it provides relevant information about pain and the NB's emotional state, allowing discrimination with non-painful stimuli. In this context, this study proposes to use Kendall's correlation coefﬁcient to quantitatively compare the relevance between the facial areas reported in literature to evaluate the NB's pain with the facial areas observed by health professionals and lay people, through eyetracking, when performing the visual pain assessment task on the NBs' facial images. The results showed that the visual perception of adults does not agree with the facial areas proposed by the literature for pain analysis. In addition, the results suggest that health professionals present a distinct perception when compared to the perception presented by non-health professionals. We believe that such results might help to improve pain assessment carried out clinically.